2011
DOI: 10.1002/qua.23182
|View full text |Cite
|
Sign up to set email alerts
|

Basis set dependence of phosphate frequencies in density functional theory calculations

Abstract: The addition of extravalence, polarization and diffuse functions, were studied in order to conclude how they affect the PAO stretching frequencies of several biological relevant phosphate molecules. The results show that the polarization and the diffuse functions have opposite effects on the frequencies: the polarization functions downshift while the diffuse functions upshift the frequencies. The effect of the valence functions was more difficult to interpret. The effect of the conductor-like screening model (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In case of the protein models, the basis set and the electron density (to make sure to obtain convergence to the same state) from the geometry optimization with Jaguar were exported to Gaussian. No scaling factor was applied to the wavenumber calculations with the large basis set since it calculates P\ \O wavenumbers which are very close to experimental results [49]: for the two PO 3 2 − -containing molecules in the studied set of molecules, the calculated wavenumbers of the asymmetric P\ \O stretching vibrations differed by only 3.3 cm −1 from experimental results (averaged absolute value of the deviations). One of these molecules was AcP.…”
Section: Dft Calculationsmentioning
confidence: 74%
See 3 more Smart Citations
“…In case of the protein models, the basis set and the electron density (to make sure to obtain convergence to the same state) from the geometry optimization with Jaguar were exported to Gaussian. No scaling factor was applied to the wavenumber calculations with the large basis set since it calculates P\ \O wavenumbers which are very close to experimental results [49]: for the two PO 3 2 − -containing molecules in the studied set of molecules, the calculated wavenumbers of the asymmetric P\ \O stretching vibrations differed by only 3.3 cm −1 from experimental results (averaged absolute value of the deviations). One of these molecules was AcP.…”
Section: Dft Calculationsmentioning
confidence: 74%
“…Frequency calculations on such large systems are computationally very expensive and it is therefore not feasible to use a larger basis set. Furthermore, Rudbeck [49] showed that even though the mean average error of the calculated P\ \O wavenumbers for the 6-31G** basis set is quite high, the phosphate geometry is reasonable. The large basis set was used for the AcP models.…”
Section: Dft Calculationsmentioning
confidence: 97%
See 2 more Smart Citations
“…The advantage of small catalytic site models over more comprehensive ones is the possibility to use large basis sets. The basis set used in our study -6-311++G (3df, 3pd) -was able to calculate the wavenumbers of two PO 3 2− containing molecules in aqueous solution with high accuracy [57]. Therefore, we decided to use this basis set without scaling the vibrational wavenumbers.…”
Section: Dephosphorylation Of the Ca 2+ -Atpase E2p Phosphoenzymementioning
confidence: 99%